The discursive construction of 'Tunisianité' (2011–2017). Issue 4 (August 2019) - Helal, Fethi
This study investigates the discursive construction of the idea of tunisianité in a sample of 41 articles published in the national press in the wake of the Arab Spring. Using analytical categories developed within the discourse-historical approach, the analysis indicates three general, strongly secularist, representations of tunisianité. One of these, which can be called essentialist, claims an unmistakable ethnolinguistic connection to a glorified pre-Arabo-Islamic classicism which goes back to the foundation of Carthage (814–146 BC). A second and a more dominant ( avowedly consensual ) one construes tunisianité in assimilationist terms, that is, Tunisia as a 'melting pot' lumping different Eastern and Western ethnolinguistic and cultural traditions. A third emerging, but a marginalized trend in the data, grounds tunisianité within the Enlightenment/Revolutionary ideals of Democracy, Dignity and Freedom and warns against its possible disintegration because of its vulnerability to the upheavals of terrorism, corporatism, populism and socioeconomic insecurity. While the third representation is laudable from the perspective of the Revolutionary demands, the dominant nationalist identity discourse remains backward-looking, reactionary and strongly preoccupied with a perceived political invasion by the Islamist-Arabist Other. It is argued that the dominant model of identity politics and the political economy associated with it are incompatible with Tunisians' aspirations for socioeconomic development and social justice.